2015
DOI: 10.1007/s11748-015-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management in myasthenia gravis: republication of a systematic review and a proposal by the guideline committee of the Japanese Association for Chest Surgery 2014

Abstract: Thymectomy is regarded as a useful therapeutic option for myasthenia gravis (MG), though perioperative management in MG patients is largely empirical. While evidence-based medicine is limited in the perioperative management of MG patients, treatment guidelines are required as a benchmark. We selected issues faced by physicians in clinical practice in the perioperative management of extended thymectomy for MG, and examined them with a review of the literature. The present guidelines have reached the stage of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 135 publications
0
11
0
Order By: Relevance
“…Four major surgical approaches are used: In all of these procedures, the thymus is resected, but the resection of extracapsular mediastinal and cervical fat tissue varies. There is no persuasive evidence of superior efficacy or long-term remission rates in MG for either of these approaches [18].…”
Section: Surgical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four major surgical approaches are used: In all of these procedures, the thymus is resected, but the resection of extracapsular mediastinal and cervical fat tissue varies. There is no persuasive evidence of superior efficacy or long-term remission rates in MG for either of these approaches [18].…”
Section: Surgical Methodsmentioning
confidence: 99%
“…Guillermo et al [17] reported that AChR antibody-positive and -negative cases have similar response rates at least 3 years follow-up, in a retrospective cohort study. Similar to anti-AChR-positive MG, generalized MG has been reported to have a double-seronegative MG as an indication for thymectomy [18].…”
Section: Seronegative Myastheniamentioning
confidence: 96%
See 2 more Smart Citations
“…International consensus and guidelines recommend all MG patients with resectable thymoma undergo thymectomy after MG is well controlled, and thymectomy is performed for the treatment of thymoma with the resection of thymus and the mediastinal and lower cervical fat (22,28,37). Although many studies have shown robotic thymectomy is safe and feasible for MG patients with early-stage thymoma, the proper size of thymoma for robotic thymectomy and the long-term oncologic outcome after robotic thymectomy are still under debate (38)(39)(40).…”
Section: Tips Tricks and Pitfallsmentioning
confidence: 99%